Torn - Hill, Casey (London Simon & Schuster, 2012)
That's Reilly Steel's mantra. Find the answers, solve the crime. But the Quantico-trained forensic investigator is finding her skills aren't enough when a ferociously intelligent killer strikes Dublin. Themodus operandi is as perplexing as it is macabre. What connects the two seemingly disparate, high-profile victims? Their corpses refuse to give up their secrets and the crime scenes prove a forensic investigator's worst nightmare. Reilly soon suspects that she may be dealing with a killer--or killers-- who know all about crime scene investigation. The police are just as frustrated by the crimes' impenetrable nature and it's only when a third murder occurs--equally graphic and elaborate in its execution--that they discover that this particular killer is using a very specific blueprint for his crimes. Who is the killer's next victim, the real target? And what's his endgame?
Include First Chapter of her new Novel named "New Reilly Steel"
Keywords: Murder--Investigation Story